The Concept of Six Capitals in Integrated Reporting – Disclosure Quality Assessment: Evidence from Poland - Boguslawa BEK-GAIK; Anna SUROWIEC (Communications of International Proceedings, 2021)
Aim / Purpose – The purpose of the paper is to identify and evaluate the quality six capitals disclosures in integrated reports published by Polish companies. The article uses the results of literature studies on the subject, the results of previous research, and observations of business practice in the area of integrated reporting. Design/methodology/approach – The quantitative and qualitative content analysis of six capitals disclosures in integrated reporting was performed in order to assess the current status of integrated reports prepared by Polish companies. The analysis covered 120 integrated reports prepared by 27 corporate groups, published from 2013 to 2020. Findings – The results of the research have shown the quality of disclosures on six capitals in the examined integrated reports. In addition, the findings proved that most of disclosures has the nature of qualitative narrations, while less attention was paid to input and output elements for every capital, and the current practice of companies regarding the disclosures on six capitals varies considerably. Originality/value/contribution – The research is aimed at presenting a critical interpretative perspective. The results of the study complement the research gap of current literature on integrated reporting.
Keywords: Integrated reporting; financial reporting; non-financial disclosure.